Modelling the EM properties of dipole reflections with application to uniform chaff clouds - Kruger, Neil (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.